ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI GARIS DAN SUDUT - Titin Suningsih; Iyam Maryati (LPPM Universitas Advent Indonesia, 2023)
The aim of the research is to analyze students' ability to understand mathematical concepts. The method applied in this research is descriptive method. The research subjects were students of class VII. The instrument used in this study was a test of students' ability to understand mathematical concepts, which amounted to 3 questions according to indicators of students' understanding of mathematical concepts. After data collection, the researcher analyzed the results of working on the ability to understand mathematical concepts and the results of the interviews to see the ability to understand students' mathematical concepts. Based on data analysis, it can be concluded that the ability to understand mathematical concepts in class VII students of SMP Negeri 1 Banjarwangi is still low, as evidenced by the presence of many mistakes in solving mathematical comprehension ability questions, especially in the indicator of restating a concept in the material lines and angles, giving examples and non-examples of concepts. , as well as on the indicators classifying objects based on whether or not the requirements that make up the concept are met or not as stated in the material lines and angles. Keywords: Ability to Understand Mathematical Concepts, Lines and Angles